(untitled) (Alternautas, 2022)
ECLAC characterises the six-year period from 1998 to 2003 as the “lost six-years” for the region. In this sense, they refer to the poor performance of the main economic variables and recall what was known at the end of the 1980s as the “lost decade”. The neoliberal discourse argued that, after the structural reforms put in place during the 1980s and 1990s, economies would grow and popular sectors would receive the spilling-over effects of that growth (the famous trickling down). It did not go like that: the growth rate of Gross Domestic Product (GDP) for the region shows a consistent decline since 1998, which reaches a critical point in 2002 due to the repercussions of the Argentine crisis. But this country was not the only one that showed the consequences of the “market policies” imposed by multilateral organisations and accepted by the local political leadership; Uruguay, Venezuela, Haiti and several countries in the Caribbean show negative annual rates of GDP growth and those that grow do so to very small degrees (ECLAC, 2003).